Polyoma virus small tumor antigen pre-mRNA splicing requires cooperation between two 3' splice sites. - Ge, H (1990)
We have studied splicing of the polyoma virus early region pre-mRNA in vitro. This RNA is alternatively spliced in vivo to produce mRNA encoding the large, middle-sized (MTAg), and small (StAg) tumor antigens. Our primary interest was to learn how the 48-nucleotide StAg intron is excised, because the length of this intron is significantly less than the apparent minimum established for mammalian introns. Although the products of all three splices are detected in vitro, characterization of the pathway and sequence requirements of StAg splicing suggests that splicing factors interact with the precursor RNA in an unexpected way to catalyze removal of this intron. Specifically, StAg splicing uses either of two lariat branch points, one of which is located only 4 nucleotides from the 3' splice site. Furthermore, the StAg splice absolutely requires that the alternative MTAg 3' splice site, located 14 nucleotides downstream of the StAg 3' splice site, be intact. Insertion mutations that increase or decrease the quality of the MTAg pyrimidine stretch enhance or repress StAg as well as MTAg splicing, and a single-base change in the MTAg AG splice acceptor totally blocks both splices. These results demonstrate the ability of two 3' splice sites to cooperate with each other to bring about removal of a single intron.